POLITIK HUKUM KEKAYAAN INTELEKTUAL KOMUNAL DALAM SISTEM HUKUM NASIONAL - Nugroho, Titis Adityo (Jurnal De Lege Ferenda Trisakti, 2024)
This study, titled "The Politics of Law in Communal Intellectual Property in the National Legal System," offers an in-depth insight into the challenges and potentials of protecting communal intellectual property (CIP) in Indonesia, a country which highly diverse in terms of ethnic groups and cultures. In this study, literature study method is used as part of a qualitative approach to understanding how the politics of law can facilitate and safeguard certain rights, especially in a national legal environment that predominantly highlights individual rights. Within the existing legal framework, this study shows that although Indonesia has taken some steps forward in CIP protection, such as the issuance of Government Regulation Number 56 of 2022, there are significant challenges remain in the implementation and effectiveness of legal protection. One of the main challenges identified is the lack of understanding and knowledge about CIP among indigenous communities. There is a need for a more comprehensive legal refinement to protect CIP, including better law enforcement and active participation from indigenous communities in policy-making and protection strategy processes. This study emphasizes the importance of considering communal perspectives in formulating and implementing legal policies related to CIP. The findings of this study provides a deeper perspective on the necessity of maintaining CIP as an integral element of national identity and a valuable asset to the country, as well as provides recommendations for improvements and enhancements in legal protection for CIP in Indonesia.